Organizational change and Laughlin (1991) framework - Yusoff, Ruslaina; Abd Rahman, Shariful Amran (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2024)
All businesses, regardless of their size, industry, or age, typically experience various processes of change. Organizational change, defined as the process of adapting to new assumptions, involves companies transforming to achieve better outcomes (Langer, Alfirevic & Pavicic, 2005). According to Smith (1982), organizational changes can be superficial or deeply affect the organization's beliefs, values, and norms. To comprehend changes within an organization, it is essential to understand its existing practices, procedures, and routines (Burns & Scapens, 2000). Organizational change occurs not only through planned initiatives that corporations undertake consciously but also through unplanned processes that happen largely unnoticed by those attempting to influence them (Beaubien, 2008; DiMaggio & Powell, 1983, p. 157). Laughlin's (1991) framework can be used to explain the change process that might occur in an organization due to any practices or processes, including corporate social and environmental reporting or sustainability reporting practices. Social and environmental issues might create disturbances to the organization’s practices, leading to changes within the organization (Larrinaga Gonzalez et al., 2001; Adams & McNicholas, 2007). According to Laughlin (1991), organizations are reluctant to change or are ‘change resistant’. However, disturbances, kicks, or jolts will lead to transformations or transitions of various intensities and durations, taking different ‘tracks’ and causing unpredictable changes. As Laughlin (1991, p. 210) suggests, organizations will only “… change when forced or ‘kicked’ or disturbed into doing something” (see also Brown & Fraser, 2006; Bebbington et al., 2009; Cho et al., 2015; Stubbs & Higgins, 2018).